THE ISLAMIC DA’WAH PROGRESSING AT THE IMPLEMENTATION OF MUHAMMADIYAH-'AISYIYAH COLLEGE EDUCATION - Masduki, Hendri; Holis, Muhammad; Iskandar, Nur; Dyanti, Siti Maisurah (Mozaic: Islamic Studies Journal, 2024)
Research includes descriptive research as a model in field research with evaluation methods (evaluative research) in order to conduct discourse aboutMuhammadiyah 'Aisyiyah College Education Governance Policy Prospectus of the Progressive Al-Islam Da'wah Movement as the context of the problem in this research. The results of the research findings show that, the management policy for the implementation of education at the Muhammadiyah 'Aisyiyah college, the prospectus of the progressive Al-Islam da'wah movement, is a real entity of the amar ma'ruf nahi munkar da'wah movement which is based on 3 (three) principle pillars (1) Humanist Principles, by prioritizing the principles egalitarian (equality) and rejecting various forms of discrimination; (2) Liberative Principles, by prioritizing selectivity by rejecting and fighting evil in various areas of life; (3) Transcendent Principle, by developing the principle of action in order to plant the seeds of goodness and spread benefits to every human being for the realization of a progressive world civilization through the provision of education. policy on the management of education at the Muhammadiyah 'Aisyiyah college, prospectus, the Al-Islam missionary movement is progressing as a movement model characterized by the existence of educational units; Islamic Boarding Schools and Islamic Boarding Schools; and the Muhammadiyah 'Aisyiyah College (PTMA) which is based on 4 (four) important pillars, namely (1) Al-Islam and Kemuhammadiyahan (AIK) as local content (MULOK) which must be taught at all levels; (2) Managerial processes using a collegial collective model in the management of education administration in accordance with the basic regulations in force in the organization; (3) Maximizing the use of cadres as human resources in the management of education in order to map the effectiveness of implementing quality standards that are competitive and able to respond to the challenges of the times; (4) Consolidation of sustainable programs involving all components in the management of education at Muhammadiyah and 'Aisyiyah universities with democratic principles; transparent; and accountable prospectus for the progressive Al-Islam missionary movement.